The Development of Thematic Teaching Materials Based on Local History Using Scientific Learning in Grade Four at Percobaan State Primary School Medan - Darwisyah I Gultom; Phil. Ichwan Azhari; Irsan Irsan (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
This research initiates from the problem of learning outcomes and student interest in learning is still low.  Thus, it triggers to conduct this research which aims to: (1) determine the effectiveness of using thematic teaching materials based on local history using developed scientific learning that can increase student positive responses and (2) Determine the effectiveness of using thematic teaching materials based on local history using scientific learning that is developed to improve student learning outcomes. It is a development research. The subjects in this study are 30 students in grade IV1 and IV2 at Percobaan state primary school Medan and the object in this study is a learning device in the form of local history-based teaching materials using scientific learning. The data collection instruments used consisted of test results and student interest in learning questionnaires. The results show that: (1) the student's response to the components and learning activities using learning tools oriented to the scientific learning model.  They have reached the specified criteria, namely the response using learning tools is positive and (2) the effectiveness of the learning tools developed using the learning model, it can be seen that the  obtained score is 86.67% viewed from the minimum moderate learning outcomes. It has exceeded the predetermined tolerance limit, which is at least 85% in moderate criteria.